The Role of Peer Education in Adolescent Girls for Stunting Prevention: A Scoping Review - Nurul Fitriyah; Sulistyaningsih Sulistyaningsih; Dewi Rokhanawati (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Stunting remains a major public health problem with long-term consequences for physical growth, cognitive development, and future productivity. Prevention efforts should begin before pregnancy, particularly during adolescence, as adolescent girls are vulnerable to anemia and may enter pregnancy with inadequate nutritional status. Although peer education is widely used in adolescent health promotion, evidence regarding its contribution to stunting prevention remains fragmented. Methods: This scoping review followed the PRISMA-ScR guideline to map evidence on the role of peer education in improving knowledge, attitudes, and behaviors related to stunting prevention among adolescent girls. The review was guided by the PCC framework, with adolescent girls as the population, peer education as the concept, and stunting prevention as the context. Literature searches were conducted in PubMed, ScienceDirect, Wiley Online Library, and Google Scholar. Studies published between 2016 and 2025 were screened using predefined inclusion and exclusion criteria, and eligible articles were synthesized narratively. Results: A total of 1,931 records were identified, of which 13 studies met the inclusion criteria. Five major themes emerged: educational media for nutrition and stunting prevention, effects of peer education on knowledge-attitude-behavior outcomes, adherence to Fe/IFA supplementation, social and environmental support, and implementation challenges. Overall, peer education demonstrated positive effects on nutritional literacy, anemia-related knowledge, preventive attitudes, and health-promoting behaviors, particularly adherence to iron supplementation. However, intervention effectiveness was influenced by teacher support, parental involvement, peer interaction, and program sustainability. Conclusion: Peer education is a promising strategy for adolescent-based stunting prevention because it strengthens knowledge, attitudes, and preventive behaviors through socially relevant communication. Its effectiveness may be enhanced when integrated into school health programs, aligned with supplementation initiatives, and supported by continuous monitoring from schools and families.